Microgeographical Variation in Dirofilaria immitis Prevalence in Dogs in Suburban and Urban Areas of Rio De Janeiro, Brazil - Chocobar, Marianna Laura Elis [UNESP]; Schmidt, Elizabeth Moreira dos Santos [UNESP]; Mendes, Ângelo Joel Ferreira; Johnson, Paul Christopher Duncan; Weir, William; Panarese, Rossella (MDPI, 2025)
Dirofilariosis, a mosquito-borne disease caused by Dirofilaria immitis and Dirofilaria repens, affects canids, felids and occasionally humans. Recent evidence suggests that D. immitis prevalence is rising in the canine populations in several areas of Brazil, even those historically considered to be non-endemic, highlighting the need for ongoing surveillance. However, prevalence studies are frequently based on inference from single diagnostic methods, and it is acknowledged that this may lead to biases and an underestimation of the disease situation. Thus, this cross-sectional study aimed to assess the prevalence of Dirofilaria spp. infection in dogs and cats across suburban and urban areas in Rio de Janeiro, Brazil. The investigation was conducted using a multi-diagnostic approach with binomial generalised linear models (GLMs) applied to investigate the association between the occurrence of infection and potential disease determinants. Blood samples from 497 dogs and 107 cats, collected at a veterinary mobile neutering unit, underwent parasitological, serological and molecular testing to detect Dirofilaria spp. infections. Among the dog samples, an overall 7.44% tested positive for D. immitis infection, while D. repens was not detected. In contrast, no cat samples tested positive for either parasite species. Prevalence was notably higher in suburban areas (14.47%) than in the urban area of Rio de Janeiro (6.17%) (p = 0.003). Dogs aged over two years had a higher risk of being infected (p < 0.001), while features such as breed, sex, size, coat type, use of macrocyclic lactones or access to outdoor spaces were not found to be predictive factors. This study reinforces the evidence that the prevalence of D. immitis is increasing in areas previously considered to have low prevalence or to be non-endemic. It also suggests that environmental and socioeconomic factors may play a key role in determining the current epidemiological status of this parasite. These findings highlight the need for increased monitoring in high-risk areas, targeted prevention and public awareness to address this emerging One Health concern.
Keywords: canine heartworm; economic disparity; environmental degradation; filarial diagnostics; mosquito-borne infection; one health; suburban areas; urban areas